Finite Element Analysis and Experimental Investigation of Cut Surface Formation of Magnetic Silicon Steel in Shear Cutting - Łukasz Bohdal (MDPI AG, 2021)
Shear cutting allows for shaping materials with any length of cutting line with high efficiency and without negative thermal effects, but it causes stresses and deformations in the cutting zone of the material. This has a negative effect on the magnetic properties of the sheet in the areas of the cut edge. The main problem on production lines is to ensure appropriate control of the process so as to obtain the appropriate technological quality of the cut edge, free of not only defects in the form of burrs and shape deviations, but also the minimum deformed zone. This task is difficult due to the large number of control variables, the influence of which on the shaping of the material and the formation of the cut edge is not fully understood. The article attempts to determine the course of the cutting process and to examine the influence of control variables on the formation of the cut edge in the shear-slitting process in which the tools perform a rotary motion. For this purpose, FEM modeling, vision techniques and experimental studies were used. A 3D model of the process was developed, which enables a detailed analysis of the states of stresses, strains, displacements and fracture mechanisms of the material. The simulation results were verified using vision techniques, which were used in the work to observe the flow and cracking mechanisms of the material. Parametric analyses were performed for the process control variables. The research showed a significant influence of the cutting velocity and the clearance between the tools on the formation of the cut edge. The most homogeneous surface of the cut edge with the minimum burr height was obtained for the following parameters: rake angle α = 15–30°, horizontal clearance hc = 0.03 mm and slitting velocity v2 = 15 m/min. The developed results can be useful for controlling the cutting process on production lines in terms of maximum process efficiency while maintaining the appropriate technological quality of the cut edge.